(untitled) (Research, Society and Development, 2016)
The Online distance learning is consolidated in the Brazilian educational system. The educational market offers courses that attract an increasing number of students seeking for professional training to get a better job position in the post-globalized labor market. This strong expansion gives rise for the concern about the quality of education offered in distance learning courses considering the market competition for drawing new students. An educational setting that features the figure of the virtual tutor (not the teacher) to act as a mediator in an online distance learning environment. Political and economic pressures for an educational democratization help the hiring of online tutors despite not having a clear understanding of neither their profile nor their duties which sprouts some doubtfulness about their performance as real mediator. These tutors are recruited to act intermediately in an online environment, which may lead them to have a supervisory performance geared to the achievement of predetermined tasks by students. This specific task may put tutors aside of an effective teaching practice, essential to build some knowledge. This article discusses the role of online assistant tutor of distance learning courses to reflect on the role of tutor as information or a knowledge manager in an educational scenario ruled by neoliberal capitalism.